Sistem Pendukung Keputusan Penerimaan Account Officer Menerapkan Metode EXPROM II (Studi Kasus: Bank Sumut) - Santri W Pasaribu; Dito Putro Utomo; Mesran Mesran (Journal of Information System Research (JOSH), 2020)
Account Officers are the main part that handles credit analysis and are required to have expertise and skills and have mastery of theoretical knowledge. The process of accepting an Account Officer (AO) is often a problem that needs to be dealt with, so far the process of accepting an Account Officer (AO) depends only on the administrative aspects or it can be said to be merely file selection without regard that applicants have the ability in that position. The need to get employees working as Account Officers (AO) is not an easy problem, many problems can be solved by using SPK. The method used in the Account Officer acceptance decision support system is the extended promethee II (EXPROM II) method. Exprom II is one of the methods of determining the order or priority in multi-criteria analysis. Exprom II compares one alternative to another and calculates the distance, the difference in alternative pairs in order to produce an output that is alternative ranking based on the highest flow value. It is hoped that the results of this study can help the bank in North Sumatra in determining the account officer who is suitable to work at the bank in North Sumatra